It Is Not Mandatory to Use Triple Rather Than Dual Anti-Platelet Therapy After a Percutaneous Coronary Intervention With a Second-Generation Drug-Eluting Stent. Issue 46 (November 2015) - Kim, Ju-Youn; Choi, Yun-Seok; Kwon, Ami; Chung, Woo-Baek; Park, Chul-Soo; Kim, Hee-Yeol; Chang, Kiyuk; Lee, Man-Young; Chung, Wook-Sung; Seung, Ki-Bae
Abstract : Abstract: It has been shown that triple antiplatelet therapy with cilostazol results in better clinical outcomes than dual therapy in patients treated with a first-generation drug-eluting stent (DES); however, it is unclear whether triple antiplatelet therapy has a similar efficacy after the implantation of second-generation DES. In the COACT (Cath Olic medical center percutAneous Coronary in Tervention) registry, 1248 study subjects who underwent percutaneous coronary intervention with an everolimus- or zotarolimus-eluting stent (Endeavor, Xience V, or Promus) were analyzed. The patients were divided into 2 groups after propensity score matching (n = 724; M = 422 [58.3%]; mean age = 66.1 ± 11.0 years): Group 1: patients treated with dual antiplatelet drugs (aspirin and clopidogrel; n = 362; M = 213 [58.8%]; mean age = 65.6 ± 11.7 years); Group 2: patients treated with triple antiplatelet drugs (aspirin, clopidogrel, and cilostazol; n = 362; M = 209 [57.7%]; mean age = 65.6 ± 11.7 years). The mean follow-up duration was 13 ± 10 months, and the cumulative incidence of major cardiovascular events (MACE) was 6.3% in Group 1 and 7.7% in Group 2. There were no significant differences in MACE (death, nonfatal myocardial infarction, and stroke) between the 2 groups (OR, 1.210; 95% CI: 0.772–1.898; P  = 0.406). Kaplan–Meier curves for MACE did not show any survival benefit for triple antiplatelet therapy, even in patients with acute coronary syndrome. In patients treated with a second-generation DES implantation, there is no added clinical benefit to using triple rather than dual antiplatelet therapy.